Рафигнатоидные клещи Крыма. II. Семейство Eupalopsellidae Willmann, 1952 - Лившиц, И.З.; Кузнецов, Н.Н. (Вестник зоологии, 1976)
The first for the USSR data concerning the fauna of the superfamily Raphignathoidea Grandjean, 1944 are presented. Characteristic of the superfamily, identification key for 6 families, characteristics of the family Eupalopsellidae Willmann, 1952, identification key for determination of genera and species of this family and an illustrated description of the species Eupalopsis maseriensis, Eupalopsellus olandicus, E. rostridius and E. trudis based on the data from the Crimea are given.